Reclaimed Water Use for Edible Crop Production in Florida - Jamie Lewis; Alan L. Wright (EDIS)
Irrigating edible crops with reclaimed water is a promising, cost-effective solution to Florida's overuse of freshwater resources. Learn more in this 4-page fact sheet written by Jamie Lewis and Alan L. Wright and published by the UF Department of Soil and Water Science, September 2011.